1978
DOI: 10.1107/s0567740878010006
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and X-ray analysis of a 1:1 adduct of hexamethylenetetramine oxide and thiourea

Abstract: A 1:1 adduct of hexamethylenetetramine oxide and thiourea (C6HI2NgO.CH4N2S)has been prepared and subjected to crystal-structure analysis. The crystals are orthorhombic, space group Pbca, with a = 7.698 (5), b = 12.03 (1), c = 23.09 (2) ,~, and Z = 8. The structure was solved by direct methods and refined with 1426 observed Cu Ka film data to R = 0.099. In the crystal lattice each (CH2)6N40 molecule is linked by O---H-N hydrogen bonds to three thiourea molecules and vice versa, giving rise to corrugated layers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…It is notable that the N−O bond length is particularly short at 1.3951(12) Å, where the normal range for the N−O distance in hydroxylammonium cations is 1.396−1.436 Å. , It is a neutral molecule, though there is a formal charge separation between nitrogen and oxygen. The structure of several adducts of urotropine- N -oxide have also been reported; we note that the molecular and crystal structure of 1 was first determined by Mak in 1978, from data accumulated at room temperature. ,
1 Molecular structure of urotropine- N -oxide.
…”
Section: Introductionmentioning
confidence: 87%
“…It is notable that the N−O bond length is particularly short at 1.3951(12) Å, where the normal range for the N−O distance in hydroxylammonium cations is 1.396−1.436 Å. , It is a neutral molecule, though there is a formal charge separation between nitrogen and oxygen. The structure of several adducts of urotropine- N -oxide have also been reported; we note that the molecular and crystal structure of 1 was first determined by Mak in 1978, from data accumulated at room temperature. ,
1 Molecular structure of urotropine- N -oxide.
…”
Section: Introductionmentioning
confidence: 87%
“…This mode of packing, in which the (CHz)6N4 moiety is not involved in hydrogen bonding and relegated to a space-filling role, has been observed for (CH2)6N40.H202.H20 and (CHz)~N40. (NHz)2CS (Yu & Mak, 1978), and appears to be a structural feature common to molecular complexes of (CHE)6N4 O.…”
Section: Structure Determination and Refinement Discussionmentioning
confidence: 93%
“…Recently we isolated and studied hexamethylenetetramine oxidet (I) and a number of its molecular adducts Yu & Mak, 1978;Mak, Ladd & Povey, 1979, and references therein). In the present work, the title compound was prepared and subjected to analysis to elucidate the nature of the molecular association.…”
Section: Introductionmentioning
confidence: 99%
“…3 H 2 0 (37), (CH2)6N40. (NH2)2CS (9), and (CH2)6N40.H202.H20 (8). The hydrogen bonding features of hydrated N,N1-dioxides 1-111 are described in the following sections.…”
Section: X-ray Crystallographic Analysismentioning
confidence: 99%
“…A research program on the structural chemistry of polycyclic tertiary amine N-oxides has been pursued in our laboratory. A series of preparative and X-ray crystallographic studies on the adducts of hexamethylenetetramine N-oxide (HMTO) have shown that all these structures involve hydrogen bonding between the terminal 0 atom of the N + 0 dative bond and the proton donor molecule(s) (7)(8)(9)(10). We now report the synthesis and structural characterization of a series of heterocyclic tertiary amine N,N '-dioxide hydrates, namely N, N '-di(o-toly1)piperazine N,N '-dioxide tetrahydrate, I, N, N '-di(p-toly1)piperazine N, N '-dioxide tetrahydrate, 11, and N,N '-di(p-chloropheny1)piperazine N,Nr-dioxide tetrahydrate, 111.…”
Section: Introductionmentioning
confidence: 99%